2022
DOI: 10.3389/fonc.2022.811374
|View full text |Cite
|
Sign up to set email alerts
|

LncRNAs, the Molecules Involved in Communications With Colorectal Cancer Stem Cells

Abstract: Colorectal cancer stem cells (CRCSCs) can actively self-renew, as well as having multidirectional differentiation and tumor regeneration abilities. Because the high functional activities of CRCSCs are associated with low cure rates in patients with colorectal cancer, efforts have sought to determine the function and regulatory mechanisms of CRCSCs. To date, however, the potential regulatory mechanisms of CRCSCs remain incompletely understood. Many non-coding genes are involved in tumor invasion and spread thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 168 publications
(184 reference statements)
0
10
0
Order By: Relevance
“…34 In the present study, we identified the transcription factors GRHL2 and BNC1 to be highly expressed A number of studies have shown that transcription factors bind to lncRNAs to promote tumor development. [21][22][23]35 Thus, we found that LINC01305 and BNC1 were specifically bound using RIP assay and RNA pull-down assay.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…34 In the present study, we identified the transcription factors GRHL2 and BNC1 to be highly expressed A number of studies have shown that transcription factors bind to lncRNAs to promote tumor development. [21][22][23]35 Thus, we found that LINC01305 and BNC1 were specifically bound using RIP assay and RNA pull-down assay.…”
Section: Discussionmentioning
confidence: 72%
“…More studies have shown that BNC1 is closely related to the occurrence of tumors, and BNC1 is upregulated by the transcription factor tumor protein P63 (TP63) in head and neck squamous cell carcinoma 19 and highly expressed by Gli protein in basal cell carcinoma 20 . Research has shown that transcription factors could not function in the process as protein forms alone, and they usually bind with lncRNAs to control the transcription of target genes 21–24 . But whether BNC1 plays its role in binding to lncRNAs in ESCC is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The circulating tumor DNA, tumor-infiltrating immune cells, and microsatellite status have emerged as promising biomarkers for the diagnosis and treatment of CRC ( 37 39 ). As an important epigenetic player in cancer pathogenesis, lncRNA together with N6-methyladenosine (m (6)A) RNA methylation has been shown to predict treatment response and disease prognosis in CRC patients ( 40 , 41 ). Epigenetic modifications have gained much attention in the research on the development of CRC, which is regarded as a diagnostic and predictive biomarker of CRC patients ( 42 , 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs are involved in a wide range of biological processes, including immune responses, a variety of disorders such as neuronal disorders, and cellular fate programs in cancer stem cells [ 27 ]. The latter plays a vital role in the origin and progression of malignancy and therapy resistance [ 28 , 29 , 30 , 31 ]. The regulatory network of lncRNAs includes EMT, drug resistance, and others via multiple mechanisms.…”
Section: Long Non-coding Rnas and Potential Therapeutic Targeting In ...mentioning
confidence: 99%
“…The regulatory network of lncRNAs includes EMT, drug resistance, and others via multiple mechanisms. LncRNAs have been shown to act as competing endogenous RNAs (ceRNAs) for specific microRNAs, thus regulating the expression of their downstream target genes [ 28 ]. LncRNAs promote cancer stem cells stemness and drug resistance [ 32 ].…”
Section: Long Non-coding Rnas and Potential Therapeutic Targeting In ...mentioning
confidence: 99%